Basic superfluids - Guenault, Tony (London: Taylor & Francis, 2003)
Superfluidity is the jewel in the crown of low temperature physics. When temperatures are low enough, every substance in thermal equilibrium must become ordered. Since some materials remain fluid to the lowest temperatures, it is a fascinating question as to how this ordering can take place. One possibility is the formation of a superfluid state, a state in which there is macroscopic quantum order-effectively quantum mechanics in a tea-cup. The author develops and presents these ideas in the beginning of Basic Superfluids. The book assumes some basic knowledge of quantum, statistical and thermal physics, and builds on this background to give a readable introduction to the three superfluids of low temperature physics. A short chapter describing experimental techniques is included. The emphasis throughout is on physical principles rather than technical detail, with the aim of introducing the subject in an accessible yet authoritative way to final-year undergraduates or starting postgraduate students.
Index 162-165p.
Keywords: Astronomy; Superfluids; Physics